واقع الاتصال الرسمي الالكتروني في المؤسسة الخدماتية:دراسة ميدانية بمؤسسة الصندوق الوطني للتأمينات الاجتماعية للعمال الاجراء وكالة النعامة انموذجا - خديمي نصر الدين (كلية العلوم الاجتماعية لجامعة مستغانم, 2023)
Abstract: Our study revolves around the issue of official electronic communication in the management of service institutions, and this prompted many researchers to focus on this topic due to the great role it plays in the management of administrative work in any institution of different nature and activity. Through this study, we tried to raise the main problem, which was represented in the reality of the electronic communication with the National Fund for Social Security for salaried workers in the state agency (Al Naama), and we used the questionnaire tool to collect and analyze data, and after arbitration by arbitrators, we distributed it to a random, intentional sample consisting of 60 samples. We relied on the survey method, and through our study we reached a set of results: * The National Fund for Social Security for Salaried Workers relies heavily on electronic communication in communicating with its employees. Human and social relations and ties between the chief and his subordinates are good. Keywords: communication, electronic official communication, institution, service, service institution.
Keywords: الاتصال الرسمي؛الاتصال الالكتروني؛المؤسسات الخدماتية